SARS-CoV-2 Oral Vaccine Design Based on Nanoparticle Encapsulation with a Combination of Chitosan and Alginate - Cista Dewi, Ni Putu Fiona; Amelia Putri, Ni Luh Dian Saptari; Sudarma, I Wayan Ari; Sang Ayu Putu Chika Iswari Anjani; Saputra, Gusti Nyoman Oka; Yowani, Sagung Chandra (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Vaccination is the most effective intervention in reducing mortality rates due to COVID-19. Oral vaccines provide a more convenient process with a dual immune response (systemic and mucosal). Encapsulation is a strategic method that can be used to enhance the efficiency of oral vaccines. The combination of chitosan and alginate can protect the drug from gastrointestinal disturbances. Our research aims to nanoencapsulate the intravenous vaccine